Targeting the ZMYM2-ANXA9 Axis with FLT3 Inhibitor G749 Overcomes Oxaliplatin Resistance in Colorectal Cancer - Dezheng Lin; Yucheng Xu; Huanmiao Zhan; Yufan Liang; Riyun Liu; Jun Liu; Dandong Luo; Xiaochuan Chen; Jiawei Cai; Yifeng Zou (Biomedicines)
Background: Chemoresistance and tumor recurrence remain major obstacles in colorectal cancer (CRC) therapy. Elucidating the molecular mechanisms underlying treatment resistance is critical for improving therapeutic outcomes. Methods: We analyzed transcriptomic profiles from public datasets (TCGA and GSE39582) to identify differentially expressed genes associated with a poor response to neoadjuvant chemotherapy in CRC patients. Among 298 candidate genes, ANXA9 emerged as significantly overexpressed in chemoresistant tumors and associated with a poor prognosis. These findings were further validated in an independent cohort of 146 Stage III CRC patients using immunohistochemistry and survival analysis. The expression of ANXA9 was evaluated in oxaliplatin acquired-resistant CRC cell lines via qPCR and Western blot. Functional studies, including RNA interference, colony formation, apoptosis assays, and drug sensitivity testing, were performed in vitro and in vivo to assess the role of ANXA9. A high-throughput drug screen identified G749, a FLT3 inhibitor, as a potential therapeutic agent. Results: ANXA9 expression was significantly elevated in non-responders to chemotherapy and oxaliplatin-resistant CRC cell lines. The knockdown of ANXA9 reduced proliferation and enhanced oxaliplatin sensitivity. G749 was found to suppress ANXA9 expression in a dose-dependent manner and inhibit CRC cell growth in vitro and in patient-derived organoids. In a CRC xenograft mouse model, G749 reduced the tumor burden without observable toxicity. Mechanistically, we identified ZMYM2 as a transcriptional regulator of ANXA9. ChIP-qPCR confirmed ZMYM2 binding to the ANXA9 promoter, especially in resistant cells. Silencing ZMYM2 suppressed tumor cell growth and restored chemosensitivity. Conclusions: The ZMYM2-ANXA9 signaling axis drives chemoresistance and tumor progression in CRC. FLT3 inhibition by G749 effectively downregulates ANXA9 and sensitizes tumors to chemotherapy, highlighting a novel therapeutic approach for chemoresistant CRC.